Effectiveness of Microvascular Decompression for Immediate Pain Relief in Trigeminal Neuralgia - Atta Ur Rehman, Sarwat Rasheed, Muhammad Haroon Bilal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aims to evaluate the immediate postoperative pain relief in patients with trigeminal neuralgia (TN) who underwent microvascular decompression (MVD), analyzing the outcomes in a cohort of 105 patients. Methods: A retrospective cohort study was conducted on 105 patients diagnosed with trigeminal neuralgia, who underwent MVD between Dec 2020 to Jan 2022. Data on immediate postoperative pain relief, demographic variables, and clinical outcomes were collected and analyzed. The primary endpoint was the immediate relief from pain measured using the Visual Analog Scale (VAS). Results: Among 105 patients, 90% experienced immediate pain relief post-surgery. The mean VAS score decreased from 8.5 preoperatively to 1.2 postoperatively. Pain relief was achieved within the first 24 hours in most patients (88%). The cohort’s average age was 57 years, with a gender distribution of 65 females (62%) and 40 males (38%). Bilateral involvement was present in 12% of cases, and vascular compression was the most common causative factor (76%). Conclusions: MVD offers significant immediate pain relief in patients with trigeminal neuralgia. The high rate of immediate postoperative relief suggests that MVD is an effective treatment for TN, particularly when vascular compression is the primary cause. Keywords: Trigeminal Neuralgia, Microvascular Decompression, Pain Relief, Immediate Postoperative Outcome, Visual Analog Scale, Vascular Compression.